Hypocalcemia Revealing an Enteropathy-Associated T-cell Lymphoma - Alonso Ortiz, Maria Belen; Villalba, Noel Lorenzo; Marroquin, Emilio Almaraz; Kechida, Melek; Mendez-Bailon, Manuel; Gonzalez, Imanol Pulido (Caspian journal of internal medicine, 2019)
Enteropathy-associated T-cell lymphoma (EATL) is a rare and aggressive type of extranodal T-cell lymphoma (TCL) arising in the gastrointestinal (GI) tract and represents 5-8% of all T-cell non-Hodgkin lymphomas (NHL) and 10-25% of primary intestinal lymphomas. We reported a 78-year-old woman presenting with severe hypocalcemia. Investigations confirmed vitamin D and iron deficiency as well as hypoalbuminemia. Celiac disease was suspected and confirmed, but despite intravenous calcium and magnesium supplementation and a gluten-free diet, normal electrolyte levels were never reached. Intestinal perforation was the clue to the diagnosis of enteropathy-associated T-cell lymphoma (EATL). Hypocalcemia can result from multiple conditions. In patients not responding to adequate supplementation, further investigations should be performed to diagnose the underlying condition.